The description of the automorphism groups of finitedimensional cyclic Leibniz algebras - Kurdachenko, L.A.; Pypka, O.O.; Subbotin, I.Ya. (Доповіді НАН України, 2022)
In the study of Leibniz algebras, the information about their automorphisms (as well as about endomorphisms,
derivations, etc.) is very useful. We describe the automorphism groups of finite-dimensional cyclic Leibniz algebras. In
particular, we consider the natural relationships between Leibniz algebras, groups and modules over associative rings. Для вивчення алгебр Лейбніца інформація про їх автоморфізми (а також про ендоморфізми, диференціювання та ін.) є дуже корисною. Описано групи автоморфізмів скінченновимірних циклічних алгебр Лейбніца. Зокрема, розглянуто природні зв’язки між алгебрами Лейбніца, групами та модулями над асоціативними кільцями.